Parenting intentions in transgender and gender‐nonconforming adults. Issue 2 (6th April 2022) - Morong, James J.; Class, Quetzal A.; Zamah, Alberuni Musa; Hinz, Erica
Abstract: Objective: To assess parenting intentions, knowledge and attitudes regarding fertility preservation, and barriers to achieving parenthood in an adult transgender population. Methods: This was a multi‐center online cross‐sectional study conducted at three university‐affiliated and 15 community‐affiliated clinics within a major US city. Inclusion criteria included being aged 18 years and older and self‐identification as transgender, gender non‐conforming or non‐binary. Eighty respondents completed a 36‐question survey regarding their transition and plans to achieve parenthood. We compared demographic characteristics to plan for transition using Chi‐Square analysis. We compared options to achieve parenthood to plans for transition using ANOVA, Spearman's rho correlation coefficient, and a Kruskal Wallis H test. Results: The mean desire to become a parent was 59.9 on a scale of 1–100. There was no significant association between plan for gonadectomy and reduced preference for the use of autologous gametes for parenting [ H (2) = 1.309, P = 0.520]. The desire to have children was correlated with an increasing willingness to pause cross‐sex hormones ( r s = 0.40, P < 0.01). Cost was identified as the largest barrier to fertility preservation (54.1%). Conclusion: The majority of transgender adults surveyed desire parenthood and this could be correlated with plan for transition including willingness to suspend cross‐sex hormones.